Late results of mitral valve replacement using unstented antibiotic sterilised aortic homografts. - Qureshi, S A (1983)
Three hundred and seventy nine patients who had undergone mitral valve replacement using unstented antibiotic sterilised aortic homografts were followed up for 52 to 138 months (mean 102 months). Patients requiring additional aortic valve replacement were excluded. The commonest cause was rheumatic heart disease (321 patients). There were 37 early deaths (9.8%) and 97 late deaths (28%). The actuarial survival of operative survivors was 83% at three years, 75% at five years, and 55% at nine years. Technical valve failure occurred in six patients (1.6%), infective endocarditis in 19 (5%), and degeneration of the valve in 43 (12.5%). The cumulative probability of freedom from endocarditis was 96% at three years, 94% at five years, and 91% at nine years, while that of freedom from valve degeneration was 97% at five years and 48% at 10 years. There were no early embolic episodes, but late embolism occurred in five patients (1.5%).